Testing for weak form efficiency of the Singapore stock market using technical analysis - Cheow, Xue Yen (2013)
Since the inception of Efficient Market Hypothesis (EMH) in the 1960s, many debates and questions have been raised about this theory. This research study has been conducted to test the weak-form efficiency of Singapore Stock Exchange (SGX) using technical analysis (TA). Daily price information of Straits Times Index (STI) for the period ranging from January 2003 to December 2012 has been extracted for the purpose of this study. Apart from using TA, a test will also be conducted to study the existence of an anomaly that is turn-of-the-month (TOM) effect, to further examine the efficiency of the market. Our results from simple moving average (SMA) and opening range breakout (ORB) have shown that Singapore stock market is weak-form efficient. However, turn-of-the-month anomaly gives an opposing view. Hence, we have concluded that Singapore stock market is weak-form efficient to a certain extent.